Systematic palaeontology of the first cretaceous fish fauna from Malaysia / Teng Yu He - Teng, Yu He (2017)
The fluvial/lacustrine red-beds in Pahang, Peninsular Malaysia, produced a fossil fish assemblage that comprises mainly isolated teeth, bone fragments and fish scales. The red-beds are equivalent to part of the Tembeling Group of Jurassic-Cretaceous age, which is distributed along the eastern part of the Central Belt of Peninsular Malaysia. Specimens have been collected from the site and prepared using mechanical matrix removal method in the Palaeontological laboratory. A total of nine taxa have been identified from approximately 100 specimens collected from the site. They are six forms of sharks (two species of Heteroptychodus, and one of Hybodus, Isanodus, Mukdahanodus and Isanodus? sp.) and three forms of ray-finned fishes (Lepidotes sp., Caturus sp. and Semionotidae genus indet). A non-marine depositional environment is implied by the presence of Heteroptychodus, Isanodus and Mukdahanodus as they have previously been found only in brackish/freshwater sediments. Heteroptychodus kokutensis, Isanodus, Mukdahanodus and Isanodus? sp. are endemic to Thailand and Malaysia, while Hybodus and Lepidotes and Caturus are cosmopolitan. This Malaysian fish fauna is closely similar to that of the Sao Khua Formation of the Khorat Group in Thailand. The Malaysian fish fauna is interpreted to be coeval with the fish fauna of the Sao Khua Formation, therefore is dated at upper Barremian to lower Aptian age. Strong similarities between these two fish faunas also indicate a possible pathway for freshwater fauna interchange between Peninsular Malaysia and the Khorat Plateau during the late Early Cretaceous.